Pluripotency of Dental Pulp Cells and Periodontal Ligament Cells Was Enhanced through Cell-Cell Communication via STAT3/Oct-4/Sox2 Signaling. (20th January 2021) - Peng, Zhengjun; Liu, Lu; Zhang, Wenyu; Wei, Xi
Abstract : Alternation in culture environment due to cell-cell communications can rejuvenate the biological activity of aged/differentiated cells and stimulate the expression of pluripotency markers. Dental pulp cells (DPCs) and periodontal ligament cells (PDLCs) are promising candidates in dental tissue regeneration. However, the molecular network that underlies cell-cell communications between dental-derived cells and the microenvironment remains to be identified. To elucidate the signaling network that regulates the pluripotency of DPCs and PDLCs, proliferation, apoptosis, cell cycle, and the expression of Oct-4/Sox2/c-Myc in DPCs and PDLCs with indirect/direct coculture were examined. PCR arrays were constructed to identify genes that were differentially expressed, and the results were confirmed by a rat model with injury. Further research on the mechanism of the related signaling pathways was investigated by overexpression/silence of STAT3, ChIP, the dual-luciferase reporter assay, and EMSA. We found that the proliferation and apoptosis of DPCs and PDLCs were inhibited, and their cell cycles were arrested at the G0/G1 phase after coculture. Oct-4, Sox2, and STAT3 expression significantly increased and PAX5 expression decreased in the coculture systems. Oct-4/Sox2/STAT3/PAX5 was actively expressed in the rat defect model. Moreover, STAT3 was directly bound to the Oct-4 and Sox2 gene promoter regions and activated the expression of those genes. Our data showed that the pluripotency of DPCs and PDLCs was enhanced through cell-cell communication. STAT3 plays essential roles in regulating the pluripotency of DPCs and PDLCs by targeting Oct-4 and Sox2 both in vitro and in vivo.